Politik Hukum Pidana Mati dan Upaya Perlindungan Hak Hidup di Indonesia: Perspektif UU Nomor 1 Tahun 2023 - Putra, Alif Arhanda (CV. Social Politic Genius (SIGn), 2025)
The regulation of capital punishment within the Indonesian legal system presents a fundamental tension with the constitutional guarantee of the right to life. Law Number 1 of 2023 introduces a new formulation necessitating an in-depth analysis of its underlying policy background and inherent protection mechanisms. This research aims to analyze the legal policy underpinning the capital punishment provisions in Law Number 1 of 2023 and to identify and analyze the forms of protection for the right to life within its application mechanism. Utilizing a normative legal research method with statute and conceptual approaches, this study qualitatively and interpretively examines relevant primary and secondary legal materials. The analysis indicates that the legal policy on capital punishment in Law Number 1 of 2023 constitutes a compromise-based